Influence of thermolysis in the nitrogen medium on physicochemical properties of medical using material based on biogenic hydroxyapatite - O. M. Otychenko; T. E. Babutina; O. R. Parkhomey; O. M. Budylina; L. S. Protsenko; I. V. Uvarova (Хімія, фізика та технологія поверхні)
Physicochemical properties and adsorbtion activity of biogenic hydroxyapatite-based (BHA) osteoapatite material and BHA alloyed by ferromagnetic particles due to using two methods of physicochemical mixing with subsequently low-temperature thermolysis in a nitrogen medium at 500 °C (below the Curie point for magnetite – 572 °C) for 2 h have been studied. The phase composition of the powders was determined using an X-ray diffractometer DRON 3.0 under CoK?-radiation. According to     X-ray studies, the material obtained by including BHA directly in the process of iron oxalate preparation had a higher intensity of Fe3O4 than such peaks of the material obtained through mechanical mixing of BHA microgranules with iron oxalate. X-ray analysis data agreed well with the data of chemical analysis which showed the Fe content of 1.17 mass. % and 1.12 mass. % at a first and second case respectively. Data of scanning microscope Jeol Superprobe 733 are evidence of uniform distribution of magnetite in BHA matrix in the both materials. Solubility experiments were performed in vitro in isotonic 0.9 % solution of NaCl with using the BHA microgranules and the powders of BHA alloyed by ferromagnetic particles placed in an incubator for 2 and 7 days at the temperature 36.6–37 °C, corresponding to the normal temperature of the human body. Both alloyed materials showed a biosolubility higher than that in BHA microgranules for the first 2 days and almost identic value for all powders after 7 days. To avoid an infection from implanted osteoapatite materials, adsorption of antibiotics is carried out by different methods. However, it is reasonable to check adsorption activity of such biomaterials preliminary for test indicators with molecular mass like that of necessary medicaments. In particular, the investigated materials were checked by using methylene blue (320 g/mol). According to the results of experiments, the presence of the alloying element influences on the adsorption properties of the investigated biomaterials at the specified concentration of methylene blue compounds solution insignificantly.